FOREIGN EXPERIENCE IN TAX REGULATION OF SOCIO-ECONOMIC PROCESSES AND POSSIBILITIES OF ITS USE IN UKRAINE (World of finance, 2021)
Introduction. In a market economy, the taxation system, determined by tax policy, has a significant impact on the socio-economic processes in the state. In the West, the development of public finance problems has long risen to a height that is unmatched in the world. Modernizing the tax system of Ukraine without Western practice, without comprehension, perception, use of such a unique scientific potential and practical experience is indispensable. At the same time, it is necessary to take into account the real conditions, national interests, historical features of our country and the creative heritage of Ukrainian scientists, the experience of domestic tax practice.The purpose of the article is to study the processes of tax regulation of socio-economic processes in countries with developed market economies, instruments of regulating the influence of the main budget-forming taxes: income tax, value added tax, excise tax and personal income tax in the context of borrowing and adapting foreign experience to Ukrainian realities.Results. The study of foreign experience in tax regulation of socio-economic processes has shown that the EU member states apply regulatory tax instruments, guided by harmonized principles and principles of fiscal solidarity. In European countries, it is permissible to provide VAT exemptions without refunding the tax credit. In the EU, VAT exemptions for small businesses are significant. At the community level, excise tax incentives for energy, alcohol and alcoholic beverages have been defined. Most countries apply them in the form of layoffs, but some in the form of reduced rates. In addition, at the discretion of the government of an EU member state, not all potential preferences may be introduced, so the list of benefits differs significantly from country to country. The unresolved problem of harmonizing the system of income taxation of legal entities does not mean that there is no opportunity to borrow the experience of tax regulation of individual countries. The policy of the governments of foreign countries (especially European ones) demonstrates the desire to exclude as much as possible exemption from income tax, however, the toolkit of investment tax credit and investment discounts, tax holidays, accelerated depreciation, tax-free funds (reserves) and differentiation of rates that have on the development of investment processes and serve to maintain a stable financial condition of economic entities. It is important to emphasize that most countries that differentiate tax rates based on profit margins use a progressive scale. In Europe, there is a tendency to socialize taxation through the introduction of a system of "family" taxation of personal income based on the differentiation of taxpayers by marital status and their actual ability to pay.Conclusions. The analysis of foreign experience of tax regulation of socio-economic development and the possibility of its adaptation to Ukrainian realities is carried out. A significant similarity of the main taxes in European countries that have common political and economic interests, historically interacting in solving global development issues, has been revealed. The mechanisms of the regulatory influence on the social and economic development of foreign countries of such taxes as VAT, excise taxes, income tax, tax on personal income have been investigated. The advantages and disadvantages of using in the world practice of taxation of various tax benefits and preferences, principles of taxation are determined. It has been substantiated due to what regulatory potential of taxes is achieved not only the fiscal efficiency of their collection, but also the leveling of the socio-economic situation of the population and the country as a whole.